Darwinism, Philosophy, and Experimental Biology Special Issue of the Journal for General Philosophy of Science - Deichman, Ute.; Travis, Anthony S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Conference proceedings of 2009 (year of Darwin) international conference on Darwin, held in Israel.
Keywords: Science -- History; Science -- Philosophy; Science, general; History of Science; Philosophy of Science